THE POWER OF HALAL LABELING: ITS IMPACT ON BRAND EQUITY AMONG COSMETIC CONSUMERS - Idaman, Northa; Fasa, Muhammad Iqbal; Putri, Siska Lusia (Journal of Halal Research, Policy, and Industry, 2024)
This study examines the influence of halal labeling on brand equity dimensions, including brand loyalty, brand identity, perceived quality, and brand image in the cosmetics industry in Indonesia. The results indicate that halal labeling significantly affects brand loyalty, with a p-value of 0.000, where consumers' trust in halal-certified products strengthens their emotional connection and preference for the brand. Halal labeling also plays a crucial role in shaping brand identity, positioning the brand within a market segment aligned with Islamic values. Furthermore, the perceived quality of halal-labeled cosmetic products is higher, as it is associated with standards of hygiene, safety, and ethical production practices, which enhance consumer satisfaction. Brand image is also positively impacted by halal labeling, with consumers viewing the brand as ethical and trustworthy. Overall, halal labeling is a vital component in strengthening brand equity in the cosmetics market targeting Muslim consumers.